Bridging global socioeconomic scenarios with policy adaptations to examine energy-water tradeoffs. (February 2021) - Absar, Syeda Mariya; McManamay, Ryan A.; Preston, Benjamin L.; Taylor, Adam M.
Abstract: Scenarios are commonly used to evaluate the environmental implications of future alternative energy pathways - they provide a benchmark for policy-makers to evaluate social, economic or environmental tradeoffs of various policies and their benefits to society. However, scenarios may leave policy-makers incognizant of potential technological hurdles, economic costs, or unforeseen environmental consequences of energy pathways, prior to venturing into long-term, binding decisions. Herein, we present a framework to bridge global socioeconomic scenarios with in situ energy policy assumptions to ensure technological alternatives can be evaluated and compared relative to realistic techno-economic constraints, environmental tradeoffs, and potential vulnerabilities arising from climate stress. We integrate downscaled Shared Socioeconomic Pathways (SSPs) with prospective Life Cycle Assessment as a framework to understand the technical specifications, i.e. raw materials, energy inputs, and environmental impacts, of alternative energy policy assumptions. We apply our integrated framework to understand the technological implications, particularly greenhouse gas emissions and water consumption, of future energy policies surrounding the practice of hydraulic fracturing in Texas, and the implications of potential adaptive responses to climate change. Results indicated that trade-offs between water conservation and greenhouse gas mitigation are inherent to hydraulic fracturing processes, necessitating careful consideration of technology options to balance environmental objectives. Highlights: The global shared socioeconomic pathways (SSPs) are extended to the local scale for Texas. Shared policy assumptions (SPAs) are developed for the energy sector for each SSP. SPAs are used to parameterize a scenario-based life cycle assessment (LCA) model. The LCA model quantifies the carbon and water footprints for technology options under each SSP.